(untitled) (Хабаршы. Психология және социология сериясы, 2025)
This article analyzes the influence of various types of identity (national, political, religious, and professional) on the level of youth trust in political institutions in the megacities of Kazakhstan. In the context of political culture transformation, urbanization, and digitalization, the issue of youth trust in state institutions is significant, as trust in government institutions indicates political stability and civic engagement in socio-political processes. The study’s methodological framework is based on a quantitative sociological analysis conducted using a representative sample (N=1598) of young people residing in Astana, Almaty, and Shymkent. An adapted institutional trust scale was employed to measure the level of institutional trust, while a multidimensional approach to social identity assessed the degree of different identity types. Data analysis was done using correlation analysis and multivariate statistical methods in SPSS software. The findings indicate that socio-economic characteristics and identification patterns determine youth trust in political institutions. Religious identity strongly influences trust in government institutions, as evidenced by its high correlation with trust in the government, the president, and local authorities. National identity also has a significant impact, particularly on trust in the parliament and government. Political identity primarily affects trust in political parties, whereas professional identity demonstrates moderate correlations with trust in all political institutions. The results confirm the hypothesis that identity type is a significant factor in shaping youth trust in state institutions. This study contributes to political sociology and youth studies by expanding the understanding of the determinants of political trust in the post-Soviet space. The practical significance of the research lies in the potential application of its findings in developing youth policies aimed at strengthening trust in state institutions and shaping political socialization strategies that account for young people’s identification characteristics. This potential impact on policy development should make the audience feel the practical relevance and importance of the study, as it provides actionable insights for policymakers and researchers in the field. Keywords: trust, youth, political institutions, identity, Kazakhstan.